DETERMINANTS OF POLITICAL VIOLENCE IN THE NORTHERN CAUCASUS: REGIONAL ASPECT - SALGIRIEV, Ali; BETILMERZAEVA, Maret; AKHTAEV, Abdulla; GAZIEV, Vakha (CENTRAL ASIA AND THE CAUCASUS, 2017)
The conflict potential in the Northern Caucasus, due to its historical complexities, has rendered it a troubled and volatile region, characterized by clashes among different political systems, diverse peoples, and ethnic groups vying for power and resources. The lack of political pluralism and freedom, coupled with poverty and social inequality, often leads to violence as a mechanism of interaction. The authors discuss various forms of political violence, exploring its nature and causes, and provide specific examples of how power elites utilize violence and the methods they employ to benefit from conflicts.The focus of the authors is on political elites, who are seen as the main decision-makers in different spheres. These elites often resort to ethnopolitical, religious, and economic rhetoric to actively participate in regional political processes. In the early 1990s, what was labeled as a rise in "national consciousness" was, in reality, increased tension and conflicts fueled by North Caucasian political and administrative elites. Moscow had to consider these elites' interests and strategies to prevent them from using mobilizing resources to incite and escalate conflicts.Regional elites frequently use political violence as a tool in their strategy, including uncompromising stances on political or religious debates, the use of force in addressing issues, economic matters, and engaging in repression and electoral violations.The authors conclude with brief recommendations on how to potentially prevent political violence in the region.